Efficacy of "Dinoprost" for detection of early non pregnancy in crossbred cows - SINHA, V K; SINGH, BALRAJ; SINHA, A K (The Indian Journal of Animal Reproduction, 2023)
Early detection of non-pregnancy was perfonned by Protaglandin induced Mille flow Test (PG-IMFT) using 2.5 mg "Dinoprost" intravenously. The drug was administered on days 20-22, 30 and 40-45post insemination. Estrus animals were included as control. The pregnancy was confirmed by per rectal palpation 45-50 days post insemination. The test was accurate in 88.23, 84.21 and 68. 75 per cent on days 40-45, 30 and 20-22 post insemination, respectively in positive cases whereas accu.–acy was 100.00 per cent in negative cases (non-pregnancy).